2005
DOI: 10.1177/0163278705275339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Statistical Significance of Health-Related Quality-Of-Life Change in Individual Patients

Abstract: Assessing individual change is feasible and potentially useful in clinical practice. This article provides an overview of the evaluation of statistically significant change in health-related quality of life (HRQOL) for individual patients. We review the standard error of measurement, standard error of prediction, and reliable change indices using a sample of 54 patients receiving care at the UCLA Center for East-West Medicine. The largest amount of change necessary for statistical significance was found for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 14 publications
1
78
0
1
Order By: Relevance
“…The RCI indicates whether change in an individual patient is beyond the measurement error of an instrument. The advantage of RCI is that it tests directly for significant individual change [12]. As expected, clinically significant changes in scores for the symptoms, emotions, physical functions, and social functions subscales were larger for the individual patients (9.23-10.67) than for the overall group (6.42-7.64 for the ''somewhat better'' group), and the RCI decreased as subscale test-retest reliability increased.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The RCI indicates whether change in an individual patient is beyond the measurement error of an instrument. The advantage of RCI is that it tests directly for significant individual change [12]. As expected, clinically significant changes in scores for the symptoms, emotions, physical functions, and social functions subscales were larger for the individual patients (9.23-10.67) than for the overall group (6.42-7.64 for the ''somewhat better'' group), and the RCI decreased as subscale test-retest reliability increased.…”
Section: Discussionsupporting
confidence: 54%
“…The reliable change index (RCI) was used to evaluate the magnitude of change in the scores that was statistically reliable and not due to random measurement error. The RCI is a function of the standard deviation and the reliability coefficient of an instrument [12]. In this study, an RCI exceeding 1.96 indicated that the postsurgery score was unaffected by random measurement error and that the change was reliable (p \ 0.05).…”
Section: Methodsmentioning
confidence: 59%
“…Anchor-based methods use a reference standard that is clinically relevant as an anchor for determining change that is important to the patient, such as the patient global rating of change (GROC). As suggested by Hays et al 43 and de Vet et al, 15 anchor-based methods estimate whether group change is big enough to be regarded as clinically important, and the concept of "minimal importance" is explicitly defined and incorporated in these anchor-based methods. Equality of the areas under the curves (AUCs) for any pair of ROC analyses was assessed using an algorithm suggested by DeLong et al 11 for dependent data.…”
Section: Discussionmentioning
confidence: 99%
“…A number of methods are available to assess statistically significant individual change [30] and clinical significance/meaningful change [31]. Ferguson et al [19] describe the use of Reliable Change Index with SF-36 data and the approach they used has been adopted within this study, but using relevant UK norm data [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Hays et al [30] describe the use of the standard error of measurement and the standard error of prediction alongside RCI. The paper emphasises the point that whichever measure is used, changes required to be significant at an individual level are much greater than those required at a group level.…”
Section: Discussionmentioning
confidence: 99%